A Comprehensive Study of Electric Vehicle Performance under Diverse Powertrain Architecture using 1D Simulation Approach - Shaiful Fadzil Zainal Abidin; Syabillah Sulaiman; Izuan Amin Ishak; Mohammad Edilan Mustafa; Saifullah Md Ghazally; Muhamad Asri Azizul (Automotive Experiences, 2026)
Electric vehicles (EVs) are becoming popular because of their potential for reducing carbon emissions and promoting sustainable transportation. However, the driving range and energy consumption performance could be a limitation on EVs' performance, which are influenced by various technical and environmental factors. This study investigates the effects of key powertrain parameters of EVs, such as battery capacity, motor efficiency, motor power, and transmission setup, on the driving range and energy consumption of EVs through simulation analysis. The Nissan Leaf and Hyundai Kona, two different EV model categories from the hatchback and Sport Utility Vehicle (SUV), were selected for analysis using 1D simulation method. The models were tested under two standardized driving cycles, which are the New European Driving Cycle (NEDC) and Worldwide Harmonised Light Vehicles Test Cycle (WLTC). The validation results showed that the absolute percentage error is less than 10 % against the key technical specifications provided by the EV manufacturers. This study considered variations in battery capacity (±30%), motor power (±30%), motor efficiency (-15% to 5%), and transmission configurations. The outcomes from this study showed that battery capacity performance, motor efficiency, and transmission gear ratio configuration significantly impacted the driving range performance. In contrast, only motor efficiency and transmission gear ratio configuration significantly contributed to energy consumption performance. This research can be considered a benchmark in optimizing EV powertrain design, which can contribute to EV development in terms of cost and productivity.